1999
DOI: 10.1016/s0010-4825(99)00017-7
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of histamine and methylhistamine kinetics: modelling and simulation approach

Abstract: In the article a model of histamine kinetics is described. A motivation of this project was to investigate the hypothesis that methylhistamine may be a marker of histamine appearance in plasma. A model has been made to support the hypothesis. Since metabolic and transport pathways of histamine and methylhistamine are complex and not very well known, the relationship between histamine and methylhistamine should be elucidated by mathematical modelling. From experimental data and the information in the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The strengths of the study include the monitoring of alcohol consumption by the participants during adolescence, as well as the collection of venous blood samples following overnight fasting, thus controlling for the effects of diet on metabolites with a rapid conversion rate. Both 1methylhistamine and creatine have a half-life of 3 h or less (Belic et al, 1999;Deldicque et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The strengths of the study include the monitoring of alcohol consumption by the participants during adolescence, as well as the collection of venous blood samples following overnight fasting, thus controlling for the effects of diet on metabolites with a rapid conversion rate. Both 1methylhistamine and creatine have a half-life of 3 h or less (Belic et al, 1999;Deldicque et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless the fact that histamine probably adopts its role as a classical signaling molecule not earlier than by postnatal day 20 [39], it is also taken up into neonatal rat astrocytes with a half time of 1.3 min [13] that is similar to its blood inactivation time of 0.5-3.5 min [40,41]. In addition, astrocytes express mRNA for HNMT, histamine degrading enzyme [13,42], which supports the notion that uptake and subsequent metabolism by glial cells of released histamine from neurons may play important role in regulating extracellular histamine concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological background for regulation mechanism was found in the literature. Therefore, the model was successfully validated, and as the model explained the measured profiles by involvement of only the two substances, it can be concluded that methylhistamine can be used as a marker for histamine release [37].…”
Section: Histamine and Methylhistamine Equilibriummentioning
confidence: 91%